Comparative study of transgenic and nontransgenic cotton. Issue 4 (11th June 2021) - Zeng, Linghe; Wu, Jixiang; Bourland, Fred M.; Campbell, B. Todd; Dever, Jane K.; Hague, Steve; Myers, Gerald O.; Raper, Tyson B.; Smith, Wayne; Zhang, Jinfa
Abstract: The environmental impact of genetically modified crops has been extensively investigated. However, few reports on the influence of transgenic traits on genetic structure have been reported in the literature. It is unknown how or if transgenic cultivars have affected genotypic variation in upland cotton ( Gossypium hirsutum L.) since its rise to dominance in cotton production. In this study, the genotypic variance components, g, of lint yield (LY) and fiber quality were compared among transgenic and nontransgenic cotton in the USDA Regional High Quality (RHQ) tests from 2002 through 2018. The popular transgenic and nontransgenic cultivars/lines developed by the major private and public cotton breeding programs in the United States during this period were included. Testing cycles within the RHQ protocol consist of standardized control cultivars plus experimental entries. Variance components were dissected in each testing year within six such testing cycles. Lint yield of the transgenic cotton was generally higher than nontransgenic cotton. Fiber quality of the nontransgenic cotton was generally higher than the transgenic cotton. For LY, the proportion of g to the total variance was lower in the transgenic cotton than in the nontransgenic cotton, but the difference diminished in the recent two cycles. The proportion of g was lower in the transgenic cotton compared with the nontransgenic cotton for fiber length, fiber strength, fiber uniformity, and micronaire. The discrepancy between the two types of cotton in the RHQ tests reflects the influences of differential breeding schemes in the private and public breeding programs on means and genotypic variance of LY and fiber quality. Core Ideas: Transgenic cotton affected genotypic variation in cotton cultivars. Differences in breeding schemes in public and private programs influenced genotypic variations. There has been an increase of genotypic variation for yield of transgenic cultivars in recent years. The yield gap between transgenic cotton and nontransgenic cotton has narrowed in recent years.